2016
DOI: 10.3389/fgene.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence as the Causal Nexus of Aging

Abstract: In this paper we present cellular senescence as the ultimate driver of the aging process, as a “causal nexus” that bridges microscopic subcellular damage with the phenotypic, macroscopic effect of aging. It is important to understand how the various types of subcellular damage correlated with the aging process lead to the larger, visible effects of anatomical aging. While it has always been assumed that subcellular damage (cause) results in macroscopic aging (effect), the bridging link between the two has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 130 publications
(155 reference statements)
1
80
0
Order By: Relevance
“…We suggest that senescent cells accumulate in HGPS after several stress events due to failure to restore p21 levels and properly reorganize heterochromatin. It has been reported that organism senescence is related to the number of senescent cells, especially in stem cell niches (Bhatia‐Dey, Kanherkar, Stair, Makarev, & Csoka, 2016). Thus, altered HDAC2 functionality may directly contribute to the accelerated aging process in laminopathic patients.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that senescent cells accumulate in HGPS after several stress events due to failure to restore p21 levels and properly reorganize heterochromatin. It has been reported that organism senescence is related to the number of senescent cells, especially in stem cell niches (Bhatia‐Dey, Kanherkar, Stair, Makarev, & Csoka, 2016). Thus, altered HDAC2 functionality may directly contribute to the accelerated aging process in laminopathic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, here, we demonstrate for the first time in vitro that UVA‐induced cellular and extracellular senescence was reflected in the simultaneous decline of epidermal germinative potential and collagen network assembly. It is reasonable to argue that early senescence phenomena described in our work are quite similar to the initial mechanisms that in vivo lead to photoaging of human skin (Bhatia‐Dey et al, ; Keyes et al, ; Keyes & Mills, ; Su et al, . In order to study the biological relevance of our skin model for use in photobiological studies, we assessed first of all the oxidative damage UVA induced.…”
Section: Discussionmentioning
confidence: 60%
“…The UVA‐induced oxidative stress in epidermal compartment induces stem cell damage that, in turn, is responsible of epidermal senescence (Panich, Sittithumcharee, Rathviboon, & Jirawatnotai, ; Youn et al, ). Cellular senescence is a form of irreversible growth arrest and apoptotic resistance and represents one of the main causes of photoaging (Bhatia‐Dey, Kanherkar, Stair, Makarev, & Csoka, ; Campisi & d'Adda di Fagagna, ). The ultimate visible effects of photoaging are irregular skin pigmentation, laxicity, and wrinkles (Fisher et al, ; Helfrich, Sachs, & Voorhees, ).…”
Section: Introductionmentioning
confidence: 99%
“…76 Cell senescence was first described >50 years ago, 77,78 and its implications for age-related disease were outlined in both the lay 79 and medical literature >20 years ago 80,81 and repeatedly implicated since. 82 Cell senescence was first shown to correlate with, [83][84][85] then to be the causal result of, telomere shortening and amenable to resetting in vitro. 86 Subsequently, resetting of telomere length was shown to reset function in aging human tissue both ex vivo 87 and in vitro, 88,89 further supporting cell senescence as a viable point of clinical intervention.…”
Section: A Systems Model For Dementiamentioning
confidence: 99%